Detection of Viruses By Counting Single Fluorescent Genetically Biotinylated Reporter Immunophage Using a Lateral Flow Assay - Kim, Jinsu (ACS Appl Mater Interfaces, 2015)
We demonstrated a lateral flow immunoassay (LFA) for detection of viruses using fluorescently-labeled M13 bacteriophage as reporters and single-reporter counting as the readout. AviTag-biotinylated M13 phage were functionalized with antibodies using avidin-biotin conjugation and fluorescently labeled with AlexaFluor 555. Individual phage bound to target viruses (here MS2 as a model) captured on an LFA membrane strip were imaged using epi-fluorescence microscopy. Using automated image processing, we counted the number of bound phage in micrographs as a function of target concentration. The resultant assay was more sensitive than enzyme-linked immunosorbent assays and traditional colloidal-gold nanoparticle LFAs for direct detection of viruses.